Efectos socio-jurídicos de la negativa a las medidas alternativas a la prisión preventiva, en los casos en que el procesado tuviera pasado judicial en el cantón Machala en el período 2011-2012. - Machuca Pogo, Juan Antonio (2016)
We currently live in an era of rapid change in the family, we witness the social core gradation in our country where parents sometimes neglect or fail the duties pertaining to the relationship parento - subsidiary, risking limb , psychological or sexual abuse of their children, so that the State intervention has been present, institutionalizing the figure of the loss of parental authority, to rescue children or adolescents, trusting their parental authority to one of its close relatives, who should play, court order office.